Toward a new twist in Hox and TALE DNA-binding specificity - Merabet, Samir; Lohmann, Ingrid (Developmental cell, 2015)
Hox proteins gain specificity by interacting with TALE-class cofactors. In a recent issue of Cell and in this issue of Developmental Cell, Crocker et al. (2015) and Amin et al. (2015), respectively, demonstrate that non-canonical Hox/TALE binding sequences play a major role in the regionalized regulation of target gene expression in vivo.
Gesehen am 16.05.2017